2016
DOI: 10.1155/2016/9294307
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Characteristics of AAA+ Protein Family Structure and Function

Abstract: Many complex cellular events depend on multiprotein complexes known as molecular machines to efficiently couple the energy derived from adenosine triphosphate hydrolysis to the generation of mechanical force. Members of the AAA+ ATPase superfamily (ATPases Associated with various cellular Activities) are critical components of many molecular machines. AAA+ proteins are defined by conserved modules that precisely position the active site elements of two adjacent subunits to catalyze ATP hydrolysis. In many case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 118 publications
(222 reference statements)
1
98
0
1
Order By: Relevance
“…An overview of the different AAA + protein clades. All AAA + proteins form higher order homo-or hetero-oligomers that form asymmetric ring structures with heterogeneous nucleotide occupancies (28)(29)(30)(31)(32)(33). All monomers contain a nucleotide binding site for ATP, and additional insertions (highlighted in orange on the monomer structures) that aid their unique functions.…”
Section: Figurementioning
confidence: 99%
“…An overview of the different AAA + protein clades. All AAA + proteins form higher order homo-or hetero-oligomers that form asymmetric ring structures with heterogeneous nucleotide occupancies (28)(29)(30)(31)(32)(33). All monomers contain a nucleotide binding site for ATP, and additional insertions (highlighted in orange on the monomer structures) that aid their unique functions.…”
Section: Figurementioning
confidence: 99%
“…We found that the mutation P504L was located at the second AAA domain (between residues 486 to 575). AAA family of domains have conserved modules which bring together active site elements of adjacent subunits for ATP hydrolysis [6]. This is required for generation of mechanical force for translocation of substrate which in case of SARS-CoV2 helicase should be the RNA duplex that needs to unwind for the replication to initiate or progress.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a mutation in this domain could have modulatory function on RNA replication by possibly modulating either the efficiency of ATP hydrolysis or the dynamics/speed of RNA unwinding. In a report by Wei et al, it was shown that a P to L mutation in the ATPase p97 showed enhanced ATPase activity [6] and desensitized this protein against its inhibitors. In another study by Lin et al it was demonstrated that a mutation from P to L in the reverse transcriptase domain of Hepatitis B virus (HBV) increased replication competency of the enzyme [8].…”
Section: Resultsmentioning
confidence: 99%
“…While a conserved sequence motif of GxxGxGK[T/S] (P-loop/Walker A motif) coordinates the α- and β-phosphates in both ATPases and GTPases (Wittinghofer, 2016), the remaining catalytic machinery, specificity determinants, and charge-compensating elements vary from enzyme to enzyme. AAA+ proteins contain four additional sequence motifs – Walker B, Sensor I, Sensor II, and second region of homology (SRH) – that contribute to ATP binding and hydrolysis along with the conserved P-loop/Walker A motif (Erzberger and Berger, 2006; Miller and Enemark, 2016). The Walker B motif (D[D/E]xx) stabilizes an essential magnesium cofactor and acts in concert with a polar residue in the Sensor I motif to orient the catalytic water for nucleophilic attack on the γ-phosphate.…”
Section: Resultsmentioning
confidence: 99%